Cyclase-associated protein 1 is a binding partner of proprotein convertase subtilisin/kexin type-9 and is required for the degradation of low-density lipoprotein receptors by proprotein convertase subtilisin/kexin type-9. (16th August 2019) - Jang, Hyun-Duk; Lee, Sang Eun; Yang, Jimin; Lee, Hyun-Chae; Shin, Dasom; Lee, Hwan; Lee, Jaewon; Jin, Sooryeonhwa; Kim, Soungchan; Lee, Seung Ji; You, Jihye; Park, Hyun-Woo; et al.
Abstract: Aims: Proprotein convertase subtilisin/kexin type-9 (PCSK9), a molecular determinant of low-density lipoprotein (LDL) receptor (LDLR) fate, has emerged as a promising therapeutic target for atherosclerotic cardiovascular diseases. However, the precise mechanism by which PCSK9 regulates the internalization and lysosomal degradation of LDLR is unknown. Recently, we identified adenylyl cyclase-associated protein 1 (CAP1) as a receptor for human resistin whose globular C-terminus is structurally similar to the C-terminal cysteine-rich domain (CRD) of PCSK9. Herein, we investigated the role of CAP1 in PCSK9-mediated lysosomal degradation of LDLR and plasma LDL cholesterol (LDL-C) levels. Methods and results: The direct binding between PCSK9 and CAP1 was confirmed by immunoprecipitation assay, far-western blot, biomolecular fluorescence complementation, and surface plasmon resonance assay. Fine mapping revealed that the CRD of PCSK9 binds with the Src homology 3 binding domain (SH3BD) of CAP1. Two loss-of-function polymorphisms found in human PCSK9 (S668R and G670E in CRD) were attributed to a defective interaction with CAP1. siRNA against CAP1 reduced the PCSK9-mediated degradation of LDLR in vitro . We generated CAP1 knock-out mice and found that the viable heterozygous CAP1 knock-out mice had higher protein levels of LDLR and lower LDL-C levels in the liver and plasma, respectively, than the control mice. Mechanistic analysis revealed that PCSK9-induced endocytosis and lysosomal degradation of LDLR were mediated by caveolin but not by clathrin, and they were dependent on binding between CAP1 and caveolin-1. Conclusion: We identified CAP1 as a new binding partner of PCSK9 and a key mediator of caveolae-dependent endocytosis and lysosomal degradation of LDLR.